Probiotic cellulose: Antibiotic-free biomaterials with enhanced antibacterial activity. (1st April 2021) - Sabio, Laura; González, Ana; Ramírez-Rodríguez, Gloria B.; Gutiérrez-Fernández, José; Bañuelo, Oscar; Olivares, Mónica; Gálvez, Natividad; Delgado-López, José M.; Dominguez-Vera, Jose M.
Abstract: The alarming increase of antibiotic-resistant bacteria, causing conventional treatments of bacterial infections to become increasingly inefficient, is one of the biggest threats to global health. Here, we have developed probiotic cellulose, an antibiotic-free biomaterial for the treatment of severe skin infections and chronic wounds. This composite biomaterial was in-depth characterized by Gram stain, scanning electron microscopy (SEM) and confocal fluorescence microscopy. Results demonstrated that probiotic cellulose consists of dense films of cellulose nanofibers, free of cellulose-producing bacteria, completely invaded by live probiotics ( Lactobacillus fermentum or Lactobacillus gasseri ). Viability assays, including time evolution of pH and reducing capacity against electrochromic polyoxometalate, confirmed that probiotics within the cellulose matrix are not only alive but also metabolically active, a key point for the use of probiotic cellulose as an antibiotic-free antibacterial biomaterial. Antibacterial assays in pathogen-favorable media, a real-life infection scenario, demonstrated that probiotic cellulose strongly reduces the viability of Staphylococcus aureus (SA) and Pseudomonas aeruginosa (PA), the most active pathogens in severe skin infections and chronic wounds. Likewise, probiotic cellulose was also found to be effective to inhibit the proliferation of methicillin-resistant SA (MRSA) . The combination of the properties of bacterial cellulose as wound dressing biomaterial and the antibacterial activity of probiotics makes probiotic cellulose an alternative to antibiotics for the treatment of topical infections, including severe and hard-to-heal chronic wounds. In addition, probiotic cellulose was obtained by a one-pot synthetic approach under mild conditions, not requiring the long and expensive chemical treatments to purify the genuine bacterial cellulose. Graphical abstract: Image, graphical abstract